Prywatyzacja sektora bezpieczeństwa militarnego - Wawrzyniak, Marcin (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
Not since today, it is known that war is a business that brings unimaginable profits, which is well recognized by equipment manufacturers and mercenaries. The concept of mercenary is nothing new to the world, you can even be tempted to say that the profession of mercenary can compete with other oldest professions for the title of “world’s oldest profession”. Modern hireling, to a large extent,differs from that in antiquity and later periods. Clientele of this type of services increased and the tasks carried by mercenaries changed. Unfortunately, often Private Military Companies (PMC) are being used for nefarious purposes.